Le « triangle du lithium » existe-t-il ? Géographie politique d’une régionalisation andine (Argentine, Bolivie, Chili) - Audrey Sérandour (Belgeo)
Media, governments and extractive companies are increasingly using the appellation "lithium triangle" to refer to South American lithium deposits in Argentina, Bolivia and Chile. Beyond its descriptive vocation, this geographical representation gives a regional dimension to the deposits, which is rarely examined. In order to consider the existence of the regional scale in the political geography of the Andean lithium, our reflection is based on the notions of regionalism and regionalization. Does the use of the appellation "lithium triangle" have a spatial translation, whether generated by political will or by more spontaneous practices? Based on a deconstruction of representation that highlights the strategies of the actors at different scales, we analyse the incompleted processes of regionalism and bottom-up dynamics of regionalization existing in this cross-border space.